Obstetric interventions among native and migrant women: a survey of episiotomy in Portugal. (13th November 2019) - Lorthe, E; Teixeira, C; Rodrigues, T; Barros, H
Abstract: Introduction: It is unclear whether migrant women experience worse pregnancy outcomes than native women. A better comprehension of obstetric care provision, including controversial interventions such as episiotomy, is important to improve equity of service provision, overall maternal and neonatal health and to support evidence-informed perinatal health policy-making. We aimed to determine if migrant and native women giving birth vaginally have different risks of episiotomy and if the risk differs by migrant sub-groups. Methods: This study is based on a cross-sectional survey of foreign-born women with a random sample of native women, implemented in 32 public maternity units in mainland Portugal. We included 3583 women with vaginal delivery. Migrant status was defined by the woman's country of birth (migrants, born abroad, vs natives, born in Portugal), then as subgroups of migrants from Brasil, Portuguese-speaking African countries (PSAC) and non Portuguese-speaking countries vs natives. The association between migrant status and episiotomy was assessed using multilevel logistic regression models, stratified by delivery mode, and adjusted for main risk factors of episiotomy. Results: The overall frequencies of episiotomy were 52.6% and 48.2% among the 1707 natives and the 1876 migrants, respectively (p = 0.01). With spontaneous delivery, migrant women had decreased odds of having an episiotomy (adjusted OR 0.70 [95% CI 0.58-0.83]), especially those from PSAC (aOR 0.57 [0.46-0.71]). However, with instrumental delivery, migrant women had increased odds of episiotomy (aOR 2.47 [95% CI 1.50-4.07]), especially those from Brasil (aOR 3.24 [1.18-8.92]) and non Portuguese-speaking countries (aOR 3.75 [1.82-7.71]). Conclusions: These results suggest non-medically justified differential care during childbirth and highlight the importance of developing evidence-based recommendations for episiotomy use, in a country with a high frequency of medical intervention during delivery. Key messages: Portugal displays a high frequency of medical interventions during delivery, including episiotomy, highlighting the need for developing evidence-based recommendations. Migrant and native women have different risks of episiotomy, suggesting non-medically justified differential care.